2009
DOI: 10.4028/www.scientific.net/jnanor.8.109
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metal Nanoparticles to Produce Yellow, Red and Iridescent Colour, from Bronze Age to Present Times in Lustre Pottery and Glass: Solid State Chemistry, Spectroscopy and Nanostructure

Abstract: Abstract. The use of metal nanoparticles dispersed in an optically clear matrix by potters and glassmakers from the Bronze Age up to the present time is reviewed from the solid state chemistry and material science point of view. The nature of metal (gold, silver or copper), the importance of some other elements (Fe, Sn, Sb, Bi) added to control metal reduction in the glass in relation to the firing atmosphere (combined reducing oxidizing sequences, role of hydrogen and water) are considered in the light of anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 107 publications
2
128
0
4
Order By: Relevance
“…The most remarkable feature of these materials is their high specular reflectance conveying to them metal-like appearance. [1][2][3][4] Although all this may suggest a product of modern nanotechnology and engineering, the fact is that the first lusters were obtained as early as 9th century A.D. in the Abbasid caliphate. 5,6 Several studies have shown that the lusters consist of a thin surface layer (several hundred nanometers thick) of metal nanoparticles, silver and/or copper with sizes ranging between 2 and 50 nm, randomly distributed within a glassy matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most remarkable feature of these materials is their high specular reflectance conveying to them metal-like appearance. [1][2][3][4] Although all this may suggest a product of modern nanotechnology and engineering, the fact is that the first lusters were obtained as early as 9th century A.D. in the Abbasid caliphate. 5,6 Several studies have shown that the lusters consist of a thin surface layer (several hundred nanometers thick) of metal nanoparticles, silver and/or copper with sizes ranging between 2 and 50 nm, randomly distributed within a glassy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Several studies have shown that the lusters consist of a thin surface layer (several hundred nanometers thick) of metal nanoparticles, silver and/or copper with sizes ranging between 2 and 50 nm, randomly distributed within a glassy matrix. [1][2][3][4] The production process [7][8][9] involves first ion exchange between the silver/copper ions (Ag þ /Cu 2þ or Cu þ ) from an initial mixture applied on the glass surface and the alkaline (Na þ and K þ ) ions from the glass, and then the nucleation and growth of metal nanoparticles through reduction of Ag þ to Ag 0 and Cu 2þ /Cu þ to Cu 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained by the C2RMF lustre team, which analysed a significant corpus of specimens, are available online 1 . A review of the main results of the other studies can be found in Philippe Colomban's paper (Colomban 2009). The composition of glaze used in the lustre decoration is highly varied with alkaline and high lead glaze.…”
Section: Nanoparticle Layermentioning
confidence: 99%
“…Like the ruby glass, the colour of the lustre decorations has a physical basis coming from metallic nanoparticles (Bobin et al 2003;Colomban 2009;Lafait et al 2009). However, lustres possess the particularity of having a colour which can change depending on the angle from which it is observed.…”
Section: Lustre Decorations Of Medieval Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation